Influence of the Primary Structural Parameters of a Precipitated SiO on the Specific Parameters of the Adsorption Isotherms of Cholesterol Dissolved in Toluene - Borivoj K. Adnadjevic; Jelena D. Jovanovic (Adsorption Science & Technology)
The influence of the primary structural parameters of the precipitated SiO 2 [globular diameter (d g ), coordination number (CN) and coalescence coefficient (CC)] on the specific parameters associated with the shapes of the adsorption isotherms [range of linearity (P), adsorption sensitivity (IS) and equilibrium adsorption capacity (a max )], the constants of the Freundlich isotherm (k and z) and the energy density distribution function parameters of the adsorption centres (β, m) was investigated. It was found that increasing the coordination number and coalescence coefficient values led to a decrease in the a max and z values, as well as in the fraction of dominant adsorption centres, while the β value and the specific amount of cholesterol adsorbed on the remained centres (a 2 ) increased. The changes in the range of linearity (P) of the adsorption isotherms were in agreement with the parameter values of the density distribution function, while the changes in adsorption sensitivity and the Freundlich constant k correlated with the changes in the specific amount of cholesterol adsorbed at the dominant adsorption centres. The optimal values for cholesterol adsorption and of the primary structural parameters of the adsorbents based on the precipitated SiO 2 were defined.